THE ROLE OF MARKETING MANAGEMENT IN BUILDING CUSTOMER VALUE AND LOYALTY IN EDUCATIONAL INSTITUTIONS - Prabowo, Galuh; Sidiq Purnomo , Muhammad; Fikri Algifari, Muhammad (As-Sulthan Journal of Education, 2024)
This research aims to analyze how the role of marketing management implemented by this madrasah is able to create value for customers and increase their loyalty. Achieving this goal is crucial as educational institutions, particularly faith-based madrasahs, not only compete in academic quality, but also in offering uniqueness and spiritual values that become the main attraction for the local community. This research method uses a qualitative approach with a case study design to explore the role of marketing management in shaping customer value and loyalty. Data were collected through in-depth interviews, observation, and documentation analysis. Thematic analysis techniques were chosen to identify key themes, providing an in-depth understanding of the marketing of faith-based education in this madrasah. The results confirm that customer loyalty is formed through responsive educational services, academic and non-academic achievements, and social activities. Responsiveness creates satisfaction, achievement increases trust, and community service strengthens a positive image. The synergy of these three factors strengthens the bond between the madrasah, students, parents and the community.